2013
DOI: 10.1186/1742-2094-10-108
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine (CX3CL1) enhances hippocampal N-methyl-d-aspartate receptor (NMDAR) function via d-serine and adenosine receptor type A2 (A2AR) activity

Abstract: BackgroundN-Methyl-d-aspartate receptors (NMDARs) play fundamental roles in basic brain functions such as excitatory neurotransmission and learning and memory processes. Their function is largely regulated by factors released by glial cells, including the coagonist d-serine. We investigated whether the activation of microglial CX3CR1 induces the release of factors that modulate NMDAR functions.MethodsWe recorded the NMDAR component of the field excitatory postsynaptic potentials (NMDA-fEPSPs) elicited in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 75 publications
4
52
0
Order By: Relevance
“…In an attempt to further evaluate the neuroprotective effect of inhibiting the CX3CR1 pathway, we studied the expression of excitatory and inhibitory synaptic scaffolding proteins, PSD-95 and gephyrin, which may suggest an imbalance in neuronal excitability as a contributor to neurodegeneration. PSD-95 and gephyrin are known to modulate excitatory and inhibitory synaptic transmission (Beique and Andrade, 2003;Prange et al, 2004;Varley et al, 2011) and the fractalkine-CX3CR1 pathway has been shown to regulate both glutamatergic excitatory and GABAergic inhibitory synaptic transmission (Lauro et al, 2008;Lauro et al, 2010;Piccinin et al, 2010;Scianni et al, 2013). In addition, in cortical brain tissues from TLE patients, modulating this pathway by adding recombinant fractalkine, decreased GABA current reduction on repeated GABA application, though, the recovery of currents to basal values was also affected, suggesting a possible desensitization of GABA receptors (Roseti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to further evaluate the neuroprotective effect of inhibiting the CX3CR1 pathway, we studied the expression of excitatory and inhibitory synaptic scaffolding proteins, PSD-95 and gephyrin, which may suggest an imbalance in neuronal excitability as a contributor to neurodegeneration. PSD-95 and gephyrin are known to modulate excitatory and inhibitory synaptic transmission (Beique and Andrade, 2003;Prange et al, 2004;Varley et al, 2011) and the fractalkine-CX3CR1 pathway has been shown to regulate both glutamatergic excitatory and GABAergic inhibitory synaptic transmission (Lauro et al, 2008;Lauro et al, 2010;Piccinin et al, 2010;Scianni et al, 2013). In addition, in cortical brain tissues from TLE patients, modulating this pathway by adding recombinant fractalkine, decreased GABA current reduction on repeated GABA application, though, the recovery of currents to basal values was also affected, suggesting a possible desensitization of GABA receptors (Roseti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Various inflammatory mediators which are known to regulate microglial activation (Cardona et al, 2006;D'Haese et al, 2012), have also been implicated in adult neurogenesis and synaptic transmission (Butovsky et al, 2006;Lauro et al, 2010;Scianni et al, 2013). Fractalkine is an inflammatory chemokine secreted by neurons and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia utilizes targeted phagocytosis for synapse organization during development and for re-organization after injury (Stevens et al, 2007, Wake et al, 2009, Tremblay et al, 2010). Microglia also modulate neuronal activity via small molecular messengers such as ATP, BDNF and CX3CL1 (Coull et al, 2005, Hayashi et al, 2006, Scianni et al, 2013, Siskova and Tremblay, 2013) thus placing microglia in the midst of an expanded paradigm—the “quad-partite” synapse (Schafer et al, 2013). In addition, microglia depend on continuous microglial-neuronal crosstalk which is mediated by neuronal ligand-microglia receptor interactions such as CX3CL1/CX3CR1, CD47/CD177, and CD22/CD45 to maintain their surveillance activities; the absence of this communication constitutes an initial “signal” to escalate/alter microglial function (Hanisch and Kettenmann, 2007, Saijo and Glass, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The release of proinflammatory cytokines can in turn increase the neuronal damage, thus creating a vicious cycle in the course of ischemic brain injury. On the other hand, through specific chemokines and their receptors, such as CD22/CD45, CD47/ CD172a, CD200/CD200R, and CX3CL1/CX3CR1, neurons and microglia can activate a series of signaling pathways and ultimately regulate neuronal apoptosis [19][20][21].…”
Section: Discussionmentioning
confidence: 99%